Single‐incision laparoscopic stoma creation: Experience with 31 consecutive cases. Issue 3 (20th May 2013) - Hasegawa, Junichi; Hirota, Masaki; Kim, Ho Min; Mikata, Shoki; Shimizu, Junzo; Soma, Yoshihito; Nezu, Riichiro
Abstract Introduction Fecal diversion may be performed using various techniques. Each technique has advantages that affect patient selection. In this report, we report our experience with 31 patients who underwent single‐incision laparoscopic stoma creation using only a pre‐selected stoma site as the point of port access. Methods A 2.5‐cm skin incision was made at a previously marked stoma site, and two 5‐mm trocars were placed into the abdomen through the stoma site. An optional third trocar was inserted at the stoma site only if the bowel needed to be mobilized or if adhesions needed to be divided. After full intra‐abdominal exploration, a selected intestinal loop was brought up to the stoma site, and the ostomy was then matured using standard techniques. Results Between April 2009 and March 2012, 31 patients (19 men) with a mean age of 68 years (range, 46–87 years) underwent single‐incision laparoscopic stoma creation. Fecal diversion included ileostomy (n = 18) and colostomy (n = 13). There were no intraoperative complications. Two patients (6.5%) required additional port placement in the midline suprapubic area. Conversion to open laparotomy was required in two patients (6.5%) because of the presence of extensive adhesions. Postoperative complications were observed in two patients and included peristomal ileus and dehydration due to high ileostomy output. Conclusions Single‐incision laparoscopic stoma creation is an effective technique that allows full intra‐abdominal visualization and bowel mobilization, while reducing the need for additional skin incisions beyond that of the stoma site.